Study on Optimization of Availability and Demand for Clean Water at Regional Drinking Water Companies (PDAM) in Jayapura City - Dwi Cahya Kurniawan; Mujiati Mujiati; Dewi Ana Rusim; Ira Widyastuti; Harmonis Rante (Publikasi Indonesia, 2024)
PDAM Jayapura is a government agency that operates in the field of providing drinking water services, apart from being a profit institution, it is also a social institution. PDAM Jayapura is tasked with providing clean water for the Jayapura City and Jayapura Regency areas. This research aims to identify the existing condition of the Jayapura City PDAM drinking water distribution system, analyze the availability, needs, and installed (distribution network) clean water needs in Jayapura City, and conduct an analysis of other alternatives in meeting Clean Water Needs in Jayapura City. The results of this research show that the coverage of clean water services by Jayapura City PDAM is still below national standards, using technological innovation to monitor and control the clean water distribution network system in real-time using sensor technology installed at each network point to identify and repair leaks quickly, based on the results of the planet 2.0 analysis, several parts of the pipe have very small velocities, therefore, the discharge coming out of the pipe is very small. The solution that can be made is to reduce the dimensions of the existing pipe so that the flow speed can be met and also by adding water pumps at various points that have a water speed of 0 m/s so that the water in the pipe can flow properly.